3D hierarchical flower-like CuCo2S4 as high energy density faradaic electrode. (2022) - George, Amala; Lonappan, Albin; Kundu, Manab
Abstract: A direct one-step solvothermal approach was developed towards the preparation of flower-like CuCo2 S4 (CCS) directly on the conductive Ni foam substrate. The morphological and structural studies of the synthesized materials were performed using XRD, HR-SEM and TEM studies, proves that the cubic spinel structured CCS flowers were decorated over the Ni foam substrate homogenously. The electrochemical performance of CCS was evaluated by cyclic voltammetry (CV), and galvanostatic charge-discharge (GCD). Benefiting from the synergistic effect between the two metal ions and special microstrual effect, resulted in an admirably high specific capacity value of 966.45C g −1 (1607.93F g −1 ) at 5 A g −1 current density, excellent rate capability at various applied current density (ranging from 5 A g −1 to 30 A g −1 ) and cycling stability upto 5000 cycles at very high current density of 5 A g −1 with 66.12% capacity retention. Hence, the binder free spinel CCS flowers demonstrated its penitential aspect as high-performance faradic electrode material for supercapacitors.